2003
DOI: 10.1080/15428110308984784
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three Methodologies for Assessing Work Activity During Computer Use

Abstract: The overall goal of this study was to evaluate three separate methodologies for gathering work activity information among computer users. These methodologies included worker self-report, work sampling, and activity monitoring. A repeated measures design was employed whereby data were collected simultaneously on each subject (n = 51) across three consecutive workdays. Exposure information gathered included keying time, mouse usage, and time spent performing various work tasks (i.e., writing, proofreading, handl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
73
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 17 publications
2
73
0
Order By: Relevance
“…This finding is in accordance with the results of other studies (15,16). However, there were no statistically significant effects of mouse and keyboard times on the prognosis of arm pain, whether self-reported or objectively recorded.…”
Section: Discussionsupporting
confidence: 83%
“…This finding is in accordance with the results of other studies (15,16). However, there were no statistically significant effects of mouse and keyboard times on the prognosis of arm pain, whether self-reported or objectively recorded.…”
Section: Discussionsupporting
confidence: 83%
“…In a recent experimental study, self reported mouse and keyboard times were shown to be 2-3 times lower than objectively measured. 13 However, the rank correlations between self reported times and objective times were 0.71 and 0.78 for mouse and keyboard times, respectively, when self reports were made at the end of the same day as the measurements were made. In real life, including retrospective assessment over longer periods, for example, four weeks, as used in the present study, these correlations may well be lower.…”
Section: Discussionmentioning
confidence: 94%
“…Homan & Armstrong (2) reported less overestimation among workers with longer durations of computer use (according to work sampling) than among workers with shorter durations of computer use. These observations seem to be in contradiction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that computer workers generally overestimate their duration of computer use at work (2)(3)(4)(5). In epidemiologic studies, the overestimation by individual participants leads to the misclassification of exposure (ie, exposure values that are too high are assigned to participants).…”
mentioning
confidence: 99%
See 1 more Smart Citation